CONSUMERS’ ATTITUDES TOWARDS BRAND PRODUCTS AND GOODS SIMILE TO BRAND PRODUCTS - Kowalczuk, Iwona; Żelazna, Krystyna (Acta Scientiarum Polonorum. Oeconomia, 2003)
In the paper there have been presented reflections on the role of brand, as a factor influencing consumers shopping behaviour. The main attention has been paid on such problems like brand value (capital) and brand influence on consumers proceeding in particular phases of decision process. Then, based on empirical researches, importance of brand in comparison with other determinants of different products choice has been showed. In connection with growing phenomenon of imitation of brand products theoretical characteristic of the problem has been presented (ways and sources of imitations), and then the results of researches pointing Polish consumers attitudes towards goods similar to brand products.